Apoptotic and antiproliferative properties of 3β‐hydroxy‐Δ5‐steroidal congeners from a partially purified column fraction of Dendronephthya gigantea against HL‐60 and MCF‐7 cancer cells. Issue 4 (16th November 2017) - Fernando, I. P. Shanura; Sanjeewa, K. K. Asanka; Kim, Hyun‐Soo; Wang, Lei; Lee, Won Woo; Jeon, You‐Jin
Abstract: Organisms belonging to the genus Dendronephthya are among a group of marine invertebrates that produce a variety of terpenoids with biofunctional properties. Many of these terpenoids have been proven effective as anticancer drugs. Here, we report the antiproliferative effect of 3β‐hydroxy‐Δ5‐steroidal congeners against the proliferation of HL‐60 human leukemia cells and MCF‐7 human breast cancer cells. The sterol‐rich fraction (DGEHF2‐1) inhibited the growth of HL‐60 and MCF‐7 cells with IC50 values of 13.59 ± 1.40 and 29.41 ± 0.87 μg ml –1 respectively. Treatment with DGEHF2‐1 caused a dose‐dependent increase in apoptotic body formation, DNA damage and the sub‐G1 apoptotic cell population. Moreover, DGEHF2‐1 downregulated the expression of Bcl‐xL while upregulating Bax, caspase‐9, and PARP cleavage in both HL‐60 and MCF‐7 cells. The steroid fraction was found to act via the mitochondria‐mediated apoptosis pathway. Identification of the sterols was performed via gas chromatography–tandem mass spectrometry analysis. Studying the mechanism of the anticancer effect caused by these sterol derivatives could lead to the identification of other natural products with anticancer properties. Abstract : The present study reports the antiproliferative effects of a partially purified column fraction from the soft coral Dendronephthya gigantea containing 3β‐hydroxy‐Δ5‐steroidal congeners against HL‐60 and MCF‐7 cells. The steroid‐rich fraction increased apoptotic body formation, DNA damage and increased sub‐G1 cell populations. These events were found to occur via the mitochondria‐mediated apoptosis pathway. The sterols were identified via gas chromatography–tandem mass spectrometry analysis.